8‐Aminoguanine Induces Diuresis, Natriuresis, and Glucosuria by Inhibiting Purine Nucleoside Phosphorylase and Reduces Potassium Excretion by Inhibiting Rac1. Issue 21 (6th November 2018) - Jackson, Edwin K.; Mi, Zaichuan; Kleyman, Thomas R.; Cheng, Dongmei
Abstract : Background: 8‐Aminoguanosine and 8‐aminoguanine are K + ‐sparing natriuretics that increase glucose excretion. Most effects of 8‐aminoguanosine are due to its metabolism to 8‐aminoguanine. However, the mechanism by which 8‐aminoguanine affects renal function is unknown and is the focus of this investigation. Methods and Results: Because 8‐aminoguanine has structural similarities with inhibitors of the epithelial sodium channel (ENaC), Na + /H + exchangers, and adenosine A1 receptors, we examined the effects of 8‐aminoguanine on ENaC activity in mouse collecting duct cells, on intracellular pH of human proximal tubular epithelial cells, on responses to a selective A1 ‐receptor agonist in vivo, and on renal excretory function in A1 ‐receptor knockout rats. These experiments showed that 8‐aminoguanine did not block ENaC, Na + /H + exchangers, or A1 receptors. Because Rac1 enhances activity of mineralocorticoid receptors and some guanosine analogues inhibit Rac1, we examined the effects of 8‐aminoguanine on Rac1 activity in mouse collecting duct cells. Rac1 activity was significantly inhibited by 8‐aminoguanine. Because in vitro 8‐aminoguanine is a purine nucleoside phosphorylase (PNPase) inhibitor, we examined the effects of a natriuretic dose of 8‐aminoguanine on urinary excretion of PNPase substrates and products. 8‐Aminoguanine increased and decreased, respectively, urinary excretion of PNPase substrates and products. Next we compared in rats the renal effects of intravenous doses of 9‐deazaguanine (PNPase inhibitor) versus 8‐aminoguanine. 8‐Aminoguanine and 9‐deazaguanine induced similar increases in urinary Na + and glucose excretion, yet only 8‐aminoguanine reduced K + excretion. Nsc23766 (Rac1 inhibitor) mimicked the effects of 8‐aminoguanine on K + excretion. Conclusions: 8‐Aminoguanine increases Na + and glucose excretion by blocking PNPase and decreases K + excretion by inhibiting Rac1.